In Vitro, Ex Vivo, and In Vivo Evaluation of the Effect of Saturated Fat Acid Chain Length on the Transdermal Behavior of Ibuprofen‐Loaded Microemulsions. Issue 6 (3rd April 2014) - Ren, Qiuyue; Deng, Chunli; Meng, Lin; Chen, Yanzuo; Chen, Liangcen; Sha, Xianyi; Fang, Xiaoling
<x xml:space="preserve">Abstract</x> In this study, the effect of the saturated fatty acid (FA) chain length in the oil phase on the behavior of Ibuprofen (IBU)‐loaded transdermal microemulsion (ME) was evaluated in vitro, ex vivo, and in vivo. Three oils classified as long (LFA), medium (MFA), and short (SFA) chain length oils, Cremophor RH40 (surfactant) and Transcutol P (cosurfactant) were selected after experimental optimization. The physicochemical properties of ME were characterized, including IBU solubility in excipients, pseudo‐ternary phase diagram construction, particle size, zeta potential, viscosity, and stability. Permeation flux and residual amount of IBU ex vivo using Franz cell system occurred in the following order: MFA‐based ME > LFA‐based ME > SFA‐based ME, which correlated well with the results of confocal scanning laser microscopy study and the in vivo retention study. The results of in vitro cytotoxicity study and skin irritation tests measured by differential scanning calorimetry were ranked in the following order: LFA‐based ME > MFA‐based ME > SFA‐based ME. Moreover, MFA‐based ME has the highest analgesic activity among all the treatment groups. MFA was found to be an optimal oil phase with appropriate FA chain length for IBU‐loaded transdermal ME, which exhibited excellent physicochemical properties, low toxicity, and good permeability profile. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci